Impedance spectroscopy and piezoresponse force microscopy analysis of lead-free (1-x) K0.5Na0.5NbO3 - xLiNbO(3) ceramics - Rai, Radheshyam
(1 - x) K0.5Na0.5NbO3 - xLiNbO(3) (where x = 0.0, 5.0, 5.5, 6.0, and 6.5 wt.%) (KNLN) perovskite structured ferroelectric ceramics were prepared by the solid-state reaction method. X-ray diffraction patterns indicate that single phase was formed for pure KNN while a small amount of second phase (K6Li4Nb10O30, similar to 3%) was present in LN doped KNN ceramics. Phase analysis indicated the change in the crystal structure from orthorhombic to tetragonal with increase in LN content. The electrical behavior of the ceramics was studied by impedance spectroscopy technique in the high temperature range. Impedance analysis was performed using an equivalent circuit model. The impedance response in pure KNN and KNLN ceramics could be deconvoluted into two contributions, associated with the bulk (grains) and the grain boundaries. Activation energies for conductivity were found to be strongly frequency dependent. The activation energy obtained from dielectric relaxation data was attributed to oxygen vacancies. From PFM we found that the composition with 6.5 wt.% LN displays stronger piezocontrast as compared to pure KNN implying an evidence of a pronounced piezoelectric coefficient. (c) 2012 Elsevier B.V. All rights reserved.